Lactate: A regulator of immune microenvironment and a clinical prognosis indicator in colorectal cancer - Zhu, Daoqi; Jiang, Yiping; Cao, Huihui; Yang, Jiabin; Shu, Yuqi; Feng, Haowei; Yang, Xiaoyu; Sun, Xiaomin; Shao, Meng (Frontiers in Immunology, 2022)
Lactate can play an immunosuppressive role in the tumor microenvironment and promote tumor development by recruiting and inducing the activity of immunosuppressive cells and molecules. High lactate concentrations are important for tumor cell metastasis, angiogenesis, and treatment resistance. However, the role of lactate in colorectal cancer (CRC) and its treatment remains unknown. In this study, lactate genes were screened based on lactate metabolism pathways. Subsequently, the lactate subtypes were determined by clustering and analysis of the subtypes at all levels, including immune checkpoints, immune infiltration, and clinical characteristics, which revealed the biological significance of lactate metabolism in CRC. Subtype-based differential gene analysis resulted in a lactate score, which stratifies the prognosis of CRC. We discovered that 27 lactate genes and 61 lactate-phenotype genes are associated with immune cell infiltration and have a significant prognostic efficacy. The CRC patients were clustered into four subtypes and five clusters, based on lactate genes and lactate-phenotype genes, respectively. There are significant differences in survival time and activities of hallmark pathways, namely immune-related signatures and chemokines, among these subtypes and clusters. Particularly, cluster 2 and subtype 1 have significantly higher lactate scores than that of the others. In conclusion, lactate score is an independent prognostic factor for cancer that can be used as a clinical guide for predicting CRC progression and as an evaluation factor for the effect of immunotherapy in CRC.